TAʿLĪM AL-ISTIMĀʿ WĀ Al-KALĀM BITAṬBĪQ USLŪB FARĪQ AL-TADRĪS FĪ AL-JĀMI'AH AL-ISLĀMIYAH AL-ḤUKŪMIYAH - Hatta Sabri; Wildana Wargadinata; Sutaman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The phenomenon of differences in educational background and linguistic abilities of new students, has an impact on the policy of the PBA IAIN Lhokseumawe study program by implementing istima' kalam learning with a team teaching strategy. This study aims to describe; What are the strategies and supporting media used by the lecturer team in learning the istima 'kalam course, in an effort to improve learning activities and students' ability to speak Arabic? This research uses a qualitative approach with the type of case study. Data were collected through in-depth interviews, participant observation and documentation studies. Then the data was analyzed by following the theory of Miles and Huberman which includes reduction after data collection, data presentation and conclusions. The results showed that there was a set of strategies used by team teaching and contributed to the achievement of the process and objectives of the istima' kalam course at the PBA IAIN Lhokseumawea. Among them are determining material that is in accordance with student competence, division of lecturers' tasks in teaching based on the stages of language proficiency competence in lectures, application of direct and indirect learning strategies both independently and in groups, with methods of summarizing, repeating, giving speeches, discussing, debating role playing.